2009
DOI: 10.1016/j.febslet.2009.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aldose reductase by dietary antioxidant curcumin: Mechanism of inhibition, specificity and significance

Abstract: Edited by Vladimir SkulachevKeywords: Aldo-keto reductase ALR2 AKR1B10 Curcumin Sorbitol a b s t r a c t Accumulation of intracellular sorbitol due to increased aldose reductase (ALR2) activity has been implicated in the development of various secondary complications of diabetes. In this study we show that curcumin inhibits ALR2 with an IC 50 of 10 lM in a non-competitive manner, but is a poor inhibitor of closely-related members of the aldo-keto reductase superfamily, particularly aldehyde reductase. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 33 publications
0
62
2
1
Order By: Relevance
“…2 and 3, which revealed that curcumin tends to adopt an entirely different configuration for each molecular target. For instance, curcumin bends only slightly and retains most of its planar structure when interacting with the minor groove of duplexed oligonucleotides (Zsila et al, 2004;Koonammackal et al, 232 2011), whereas it becomes entirely nonplanar and often rotates around the longitudinal axis when interacting with, e.g., the C1B domain of PKCu (Majhi et al, 2010;Das et al, 2011), PfATP6 (Ji and), aldose reductases (Muthenna et al, 2009;Katsori et al, 2011), and beta amyloid peptides (Ngo and Li, 2012). As a result, curcumin is able to associate with a plethora of biomolecules due to its structural adaptability, which is "exploited" to maximize the number of interatomic bonds between curcumin and its target.…”
Section: H-bond Accepting Capacity Of the Methoxy Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 and 3, which revealed that curcumin tends to adopt an entirely different configuration for each molecular target. For instance, curcumin bends only slightly and retains most of its planar structure when interacting with the minor groove of duplexed oligonucleotides (Zsila et al, 2004;Koonammackal et al, 232 2011), whereas it becomes entirely nonplanar and often rotates around the longitudinal axis when interacting with, e.g., the C1B domain of PKCu (Majhi et al, 2010;Das et al, 2011), PfATP6 (Ji and), aldose reductases (Muthenna et al, 2009;Katsori et al, 2011), and beta amyloid peptides (Ngo and Li, 2012). As a result, curcumin is able to associate with a plethora of biomolecules due to its structural adaptability, which is "exploited" to maximize the number of interatomic bonds between curcumin and its target.…”
Section: H-bond Accepting Capacity Of the Methoxy Groupsmentioning
confidence: 99%
“…References used in Fig. 3: [1] (Yoo and Medina-Franco, 2011); [2] (Muthenna et al, 2009);[5] (Milacic et al, 2008); [9] (Ngo and Li, 2012); [10] ; [11] (Majhi et al, 2010); [12] (Mamidi et al, 2012); [13] (Das et al, 2011);[15] (Bustanji et al, 2009). The data set has been included in Supplemental Table 1. 230 distances between curcumin and several amino acid residues ($2.7 Å), indicating that the metal-diketone interaction is quite significant in the binding of curcumin to HIV-1 integrase.…”
Section: H-bond Accepting Capacity Of the Methoxy Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the search for AKR1B1 inhibitors is an active field of research. However, the clinical use of various compounds, including tolrestat (Drugbank ID DB02383) and sorbinil (Drugbank ID DB02712) has been hampered by their poor effectiveness and severe adverse effects, such as hepatitis or renal toxicity, attributed to inhibition of the related enzyme aldehyde reductase (AKR1A1 or ALR1) (Muthenna et al, 2009). Therefore, inhibitor selectivity for AKR1B1 over AKR1A1 is preferred over inhibitory potency if it implies fewer side effects (Suzen and Buyukbingol, 2003).…”
Section: Introductionmentioning
confidence: 99%